The development of linktree-assisted e-module based on CTL to improve IPAS learning outcomes - Achmad, Nadia Fajrina; Tyas, Dewi Nilam (Jurnal Prima Edukasia, 2026)
Abstract: Students’ low learning outcomes on the topic of “Magnetic Force” were caused by conventional teaching methods and limited availability of innovative and contextual teaching materials. The objective of this study is to develop and evaluate the feasibility and effectiveness of a Linktree-assisted CTL-based e-module in improving the learning outcomes of fourth-grade students in IPAS subject. A Research and Development (R&D) approach was utilized in this research, following the adaptation of the Borg and Gall model consisting of ten systematic stages in product development. The research subjects included material expert, media expert, classroom teacher, and students. To carried out the data collection process, a combination of questionnaires, documentation, and interviews was employed. To analyze the collected data, several techniques were utilized, including descriptive analysis, normality tests, t-tests, and N-gain tests. The design validation results showed a very feasible category from material expert (87%) and media expert (98%). The analysis of the response questionnaires yielded scores of 96.61% for students and 97.50% for teachers, placing both within the “very feasible” range. The effectiveness of the e-module was demonstrated by the t-test results with a significance value of 0.000, leading to the rejection of H0 and the acceptance of Ha, as well as an N-gain value of 0.5489, which considered “moderate”. Thus, the Linktree-assisted CTL-based e-module was a highly feasible and effective digital teaching material innovation to improve the learning outcomes of fourth-grade students in IPAS subject, particularly on the topic of “Magnetic Force”. Furthermore, the developed e-module serves as a highly effective digital innovation that aligns with modern educational needs. Keywords: e-module, Linktree, CTL, learning outcomes